(untitled) (Medicine Today, 2017)
Despite the proven benefits, laparoscopic colorectal surgery is still under utilized among surgeons. Aim of this study is to determine the feasibility and morbidity after laparoscopic Total Mesorectal Excision(TME), implementing a standardized operative technique and recovery protocol. The first 30 patients treated laparoscopically were included. Standardized oncological clearance ensured by early central vascular ligation, medial to lateral approach, and complete mesorectalexcision. Recovery parameters, short-term outcomes, morbidity and mortality have been assessed.Total number of patient was 30. In 26 patients anterior resection was done, in 4 patients Abdominoperineal resection was done.Overall mean operating time was 224( 242-137) minutes. In anterior resection Mean operating time was 187( 236-137) minutes, whereas in lap APR operating time was 210(242-178) minutes. In total 4 patients(13%) were converted to open procedure. Average bleeding in anterior resection group was 120 ml( 50-200ml), in Lap APR 210 ml(115-350ml). Mean number of lymphnodes removed in AR 16. In APR1, Mean time to flatus was 1.5 days. Mean time to stool 4.2 days, mean length of hospital stay in AR 8.6 days, in APR 11.5 days. Overall morbidity 23%(7), major morbidity 10%(3). There is no mortality, no anastomotic leak, and no 30 days readmission.laparoscopic Total Mesorectal Excision is safe and leads to excellent results in terms of recovery and short term outcomes. Key factors for better outcomes is adoption of a standardized technique and training model. Medicine Today 2016 Vol.28(2): 75-78